Public Health, Laboratory Experiment, and Asymptomatic Carriers in Japan, ca. 1920–1950. Issue 1 (1st March 2019) - Suzuki, Akihito
Abstract: From the 1920s and 1930s, discussion of asymptomatic carriers started to appear in Japan and quickly became well established. Two important frameworks here were public health and laboratory experiment. Japanese public health policies existed in theory, isolating asymptomatic carriers within their own family to prevent infection of others. These theoretical policies did not, however, attract great attention either from doctors, carriers, or family members. The crucial aspect in Japan was laboratory experiment. Japanese doctors concentrated on experimenting with animals as carriers of typhoid and other asymptomatic infections, trying to incorporate the latest theories of life and death taken from physiology. One reason for the relative neglect of the public health and isolation policy was the ongoing presence of a large number of patients with such diseases; another was the prestige of the laboratory as intellectual authority among well-trained doctors.